Therapeutic effects of bunga kantan (Etlingera elatior) flower aqueous extract on streptozotocin-induced diabetic sprague-dawley rats - Nawi, Afifah (Universiti Sains Malaysia, 2017)
Diabetes mellitus (DM) is a concerning non-communicable disease worldwide that has great socio-economic impact especially in Malaysia where the prevalence beats global figure. Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder characterised by hyperglycaemia leading to overproduction of oxidative stress that causes multiple complications. Oxidative stress is associated with its pathogenesis and hyperglycemia may cause cardiovascular complications. Paederia foetida (Rubiaceae) is an edible plant found in Asian countries, traditionally used to treat various diseases, including diabetes as it has anti-inflammatory, antioxidant, and antidiabetic properties. However, the role of Paederia foetida twigs in diabetic cardiomyopathy has not been reported yet. This study was conducted to determine the antioxidant, anti-inflammatory, and antiapoptotic effects of Paederia foetida twigs in high-fat diet streptozotocin-induced type-2 diabetes mellitus in Sprague Dawley rats. Forty-eight (48) male Sprague Dawley rats were acclimatized for a week. Out of 48 rats, 8 rats were assigned to normal control, while 40 rats were induced with obesity using a high-fat diet for 4 weeks. Out of 40 obese rats, 32 were induced with Type 2 diabetes Mellitus (T2DM) rats using 40mg/kg streptozotocin (intraperitoneally). The thirty-two (32) diabetic rats were further sub-divided into 4 groups; diabetic control, and three groups treated with 300mg/kg metformin, 50mg/kg, and 100mg/kg Paederia foetida respectively. Paederia foetida and metformin were orally administered to the rats for 28 days. Body weight, fasting blood glucose, and food intake were taken every week. The rats were sacrificed after four weeks of treatment using 200 mg/kg of sodium pentobarbital. The blood samples were collected by cardiac puncture and serum was prepared and analyzed for lipid profile and blood glucose levels. The heart was surgically removed, and the homogenate was prepared in an ice-chilled 10% potassium chloride solution. Three antioxidant enzymes (Superoxide dismutase (SOD), Glutathione peroxidase (GPx) and Catalase (CAT) and two oxidative stress markers (Malondialdehyde ( MDA ) & protein carbonyl ( PCO ) were measured along with proapoptotic (BAX and caspase-8) and antiapoptotic (Bcl-2) markers. Hematoxylin & Eosin and Masson’s Trichrome staining were done to visualize the histomorphological changes in the heart tissues of diabetic rats. Daily single oral administration of 50mg/kg Paederia foetida twigs on diabetic rats for 28 days revealed this dosage as the most effective in lowering blood glucose (27.2%), which is comparable to 300mg/kg metformin (23.1%). The antioxidant activity of the extract is demonstrated by its ability to inhibit lipid peroxidation and enhance levels of SOD, GPx, and CAT. In diabetic rats, the heart exhibit typical signs of diabetic cardiomyopathy, including cardiomyocyte hypertrophy, fibrosis, and perivascular fibrosis. Supplementation of Paederia foetida or metformin helps to safeguard against the histopathological and biochemical alterations associated with diabetic cardiomyopathy. In a nutshell, this study suggests that Paederia foetida managed to produce positive data on diabetic cardiomyopathy in rats through its antihyperglycaemic and antioxidative properties.